Endovascular Treatment of Wide-Neck Intracranial Aneurysms Using the Novel Contour Neurovascular System: 5-Year Follow-Up - Ktayen, Howra; Akhunbay-Fudge, Christopher Yusuf; Tyagi, Atul Kumar; Deniz, Kenan; Patankar, Tufail (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: The Contour neurovascular embolization device is a novel way to treat wide-neck bifurcation aneurysms (WNBA), which often pose considerable treatment challenges. In this study, we aim to evaluate the efficacy and safety profile of this device.MATERIALS AND METHODS: Prospective clinical and radiologic data were collected for all patients treated with the Contour device at our center, between January 2017 and December 2018. All patients were treated electively, and aneurysms were unruptured.RESULTS: Fourteen patients were recruited, and the device was successfully deployed in 11 patients. All patients were women with a mean age of 65 years. Four basilar tip, 2 internal carotid, 3 middle cerebral, 1 anterior communicating, and 1 superior cerebellar artery aneurysms were treated. The mean aneurysmal size was 6 mm (width) × 7.6 mm (height), with 4.1 mm neck. Follow-up imaging included DSA, MRA, and CTA. For the 9 patients available at year 2 follow-up, 5 showed improved occlusion class over time with 8 of 9 having adequate occlusion defined by class 1 and 2 of the Raymond-Roy (R-R) classification system. Eight patients were available for 3-year follow-up: 7 patients had stable occlusion class including 3 patients with stable complete occlusion (R-R class 1). One patient had worsening of R-R occlusion class from 1 to 2 and subsequently presented with acute subarachnoid hemorrhage. Follow-up data 5 years after implantation were available for 8 patients (including the ruptured and re-treated patient): 7 patients had adequate occlusion (R-R class 1 and 2), however, 1 patient had worsened from R-R class 1 to R-R class 2. Four patients had complete occlusion.CONCLUSIONS: Results demonstrate progressive occlusion of wide-neck aneurysms over the first 2 years, but we have also demonstrated worsening of R-R occlusion class in some aneurysms that were previously completely occluded. Our results suggest that the Contour device is a good option in WNBA, however, it appears that patients must be followed up for a minimum of 5 years.CNSContour Neurovascular SystemGCSGlasgow Coma ScaleR-RRaymond-RoyWEBWoven EndoBridgeWNBAwide-neck bifurcation aneurysms